2020
DOI: 10.1021/acs.chemrestox.0c00075
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Perfluorooctanesulfonate and 6:2 Chlorinated Polyfluorinated Ether Sulfonate with Human Serum Albumin: A Comparative Study

Abstract: 6:2 Chlorinated polyfluorinated ether sulfonate (6:2 Cl-PFESA) possesses a similar structure to perfluorooctanesulfonate (PFOS) and is the third most important polyfluoroalkyl/perfluoroalkyl substance (PFAS) found in the general population of China. Studies have indicated that 6:2 Cl-PFESA exhibits a stronger bioaccumulative and toxicological potential than PFOS and is thus of considerable environmental concern. Here, the binding characteristics of PFOS and 6:2 Cl-PFESA to human serum albumin (HSA) were explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…65 In addition, 6:2 Cl-PFESA can induce liver enlargement, injury and disturb lipid metabolism at low doses, and can bind to human serum albumin with stronger affinity compared with PFOS. 66 Significant positive correlations between PFASs were observed, especially PFHxS-PFHpS, PFHxS-PFOS, and PFHpS-PFOS, from 1998 to 2008. In addition, 8:2 Cl-PFESA, as an impurity of 6:2 Cl-PFESA production, 67 was positively correlated with 6:2 Cl-PFESA in 1998−2008.…”
Section: ■ Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…65 In addition, 6:2 Cl-PFESA can induce liver enlargement, injury and disturb lipid metabolism at low doses, and can bind to human serum albumin with stronger affinity compared with PFOS. 66 Significant positive correlations between PFASs were observed, especially PFHxS-PFHpS, PFHxS-PFOS, and PFHpS-PFOS, from 1998 to 2008. In addition, 8:2 Cl-PFESA, as an impurity of 6:2 Cl-PFESA production, 67 was positively correlated with 6:2 Cl-PFESA in 1998−2008.…”
Section: ■ Discussionmentioning
confidence: 90%
“…Animal studies have shown that environmentally relevant concentrations of 6:2 Cl-PFESA can decrease the heart rate in avian embryos and enlarge liver mass in hatchings . In addition, 6:2 Cl-PFESA can induce liver enlargement, injury and disturb lipid metabolism at low doses, and can bind to human serum albumin with stronger affinity compared with PFOS . Significant positive correlations between PFASs were observed, especially PFHxS-PFHpS, PFHxS-PFOS, and PFHpS-PFOS, from 1998 to 2008.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the complexity of the multiple binding sites and the flexible conformations of different pockets for the binding of the ligand to HSA. Recently, Sheng et al proposed that PFOS and 6:2 Cl-PFESA, an alternative of PFOS, showed preferential binding to different binding sites of HSA based on the binding measure of designed core peptides. Therefore, the use of single conformation of complexes, such as the crystal structure of PFOS-HSA (PDB ID: 4E99), may be insufficient to rank the binding strength of mixed linear and nonlinear PFAS based on the docking score evaluations in Sudlow site II in subdomain IIIA (fatty acid 3/4 site), although this site has been demonstrated to be a major binding site for linear PFOS in the previous reports. , …”
Section: Resultsmentioning
confidence: 99%
“…6:2 Cl‐PFESA was a substitute for PFOS and may have more potent reproductive toxicity that affected the birth weight of newborns (Chu et al, 2020); it was related to reduced hepatitis B virus surface antibody levels in adults, and it can cause liver damage in mammals (Wang et al, 2020; Zeng et al, 2020). Moreover, the ability of 6:2 Cl‐PFESA to bind to serum protein was stronger than that of PFOS (Sheng et al, 2020). In our results, it was not difficult to discover that 6:2 Cl‐PFESA has always been negatively correlated with immune cells (WBCs, LYMs, MONs, NEUs).…”
Section: Discussionmentioning
confidence: 99%